Sistem Pendukung Keputusan Pemilihan Salesman Marketing Terbaik Menggunakan Metode AHP - Zulfi Azhar (JURIKOM (Jurnal Riset Komputer), 2019)
PT. Anugerah Karya Abiwara is a company engaged in motorcycle sales. Today the company continues to experience rapid progress and already has a sufficient number of employees. This company requires choosing the best marketing salesman who can later be promoted to a sales supervisor. In determining the best marketing salesman, company leaders usually judge only by looking at the amount of sales turnover from each marketing salesman. It does not pay attention to other factors that influence in supporting a fair assessment. . Decision support system is a system that is very suitable and in accordance with these problems. In this study using the Analytical Hierarchy Process (AHP) method which is a method using several criteria and a number of alternatives that have been determined. Based on the results of the analysis conducted, the selected criteria are intellectual capacity and the first alternative is the best marketing salesman.